30 Dissociation and its biological and clinical correlates in functional neurological disorder: a systematic review and meta-analysis. Issue 12 (14th November 2022) - Campbell, Malcolm C; Smakowski, Abigail; Rojas-Aguiluz, Maya; Goldstein, Laura H; Cardeña, Etzel; Nicholson, Timothy R; Reinders, Antje ATS; Pick, Susannah
Abstract : Objectives/Aims: Dissociation is a potential mechanism in FND. Although scientific studies report elevated rates of dissociative symptoms in FND, a systematic assessment of the biological and clinical correlates of dissociation in FND is lacking. We aimed to systematically review the current evidence describing dissociative symptoms and disorders in functional neurological disorder (FND), and additionally conduct a meta-analysis of dissociative symptom severity in FND. We also aimed to synthesise the existing data on biological and clinical correlates of dissociation in FND. Methods: We systematically searched Embase, PsycINFO, and Medline, combining terms for FND and dissociation. Studies were eligible for inclusion if reporting on dissociative symptom scale scores or rates of dissociative disorder in FND samples. Studies were appraised for methodological quality using modified Newcastle-Ottawa criteria. Findings pertaining to dissociative symptoms or disorders, as well as biological and clinical correlates of dissociation in FND samples, were synthesised qualitatively. Dissociative symptom scores were included in a meta-analysis using random and mixed effects models. Results: Two-thousand and eighty-eight records were screened and seventy-nine studies were included in the final review. Dissociative symptoms were elevated in FND. The meta-analysis demonstrated a significant elevation in dissociation in FND samples relative to neurological and healthy controls, but not psychiatric controls. Dissociative disorders were frequently co-morbid in FND samples. Psychoform (cognitive) dissociation was more prominent in FND-seizures, whereas somatoform (physical) dissociation tended to be more prominent in FND-motor symptom samples. Dissociation was associated with FND symptom severity or frequency, general psychopathology, and reduced quality of life. Biological correlates of elevated dissociation included structural and functional brain alterations in regions that have previously been implicated in FND, such as the anterior cingulate cortex. Conclusions: Dissociative symptoms and disorders are common in FND, and different FND subgroups appear to endorse varying degrees of psychoform or somatoform dissociation. Presence of dissociative symptoms in FND is associated with adverse clinical features; there is therefore a clinical need to assess patients with FND for dissociative symptomatology and to address these symptoms during treatment. Future research should examine dissociation further in different FND subgroups, using measures that distinguish between different types of dissociation, alongside measures of underlying pathophysiology.